Preparation of Margarines from Organogels of Sunflower Wax and Vegetable Oils. Issue 10 (16th September 2014) - Hwang, Hong‐Sik; Singh, Mukti; Winkler‐Moser, Jill K.; Bakota, Erica L.; Liu, Sean X.
Abstract It was previously reported that sunflower wax (SW) had high potential as an organogelator for soybean oil–based margarine and spread products. In this study, 12 other vegetable oils were evaluated in a margarine formulation to test feasibility of utilization of SW as an alternative to solid fats in margarine and spread products containing these oils. The minimum quantity of SW required to form a gel with these oils ranged from 0.3% to 1.0% (wt.). Organogels were prepared from the vegetable oils with 3%, 5% and 7% SW and were tested for firmness as well as melting behaviors using differential scanning calorimetry. These organogels were also incorporated into a margarine formulation. All of the vegetable oil organogels produced relatively firm margarines. The margarines prepared from organogels containing 3% (wt.) SW had greater firmness than commercial spreads, whereas margarines made from 7% SW were softer than commercial stick margarines. However, dropping points of the margarine samples were higher than those of commercial spread and margarine products. Margarine firmness was modestly inversely correlated with the amount of polar compounds in the oils and did not correlate with fatty acid compositions. This study demonstrates the feasibility of using a number of healthy vegetable oils rich in polyunsaturated fatty acids to make healthy margarine and spread products by utilizing SW as an organogelator.